Autophagy and misfolded proteins in neurodegeneration - Metcalf, Daniel J. (Academic Press, 2012)
The accumulation of misfolded proteins in insoluble aggregates within the neuronal cytoplasm is one of the common pathological hallmarks of most adult-onset human neurodegenerative diseases. The clearance of these misfolded proteins may represent a promising therapeutic strategy in these diseases. The two main routes for intracellular protein degradation are the ubiquitin–proteasome and the autophagy–lysosome pathways. In this review, we will focus on the autophagic pathway, by providing some examples of how impairment at different steps in this degradation pathway is related to different neurodegenerative diseases. We will also consider that upregulating autophagy may be useful in the treatment of some of these diseases. Finally, we discuss how antioxidants, which have been considered to be beneficial in neurodegenerative diseases, can block autophagy, thus potentially compromising their therapeutic potential.